Towards magnesium alloys for high-volume automotive applications. (February 2017) - Joost, William J.; Krajewski, Paul E.
Abstract: Reducing vehicle weight is an important approach for increasing fuel economy, addressing regulatory requirements, and meeting consumer needs. Magnesium alloys are among the lightest structural metals and offer tremendous weight saving potential; however, many technical and commercial barriers limit their use in today's cars and trucks. Following a brief review of historical trends in vehicle weight and automotive magnesium, we describe key barriers to wider adoption of magnesium in high-volume vehicle applications. A discussion of manufacturing and processing, in-service performance, and cost requirements identifies specific development needs and opportunities while framing promising paths forward. Graphical abstract: